A study of new methods and techniques for ultrasonic attenuation estimation - Zenteno Valdiviezo, Omar Jonathan (Pontificia Universidad Católica del Perú, 2017)
The pathological states of biological tissue are often related in attenuation changes of itself. Thus, information about attenuating properties of tissue is valuable for the physician and could be useful in ultrasonic diagnosis. However, accurate characterization of tissue pathologies using ultrasonic attenuation is strongly dependent on the accuracy of the algorithm that is used to obtain the attenuation coefficient estimates. In the present document, we derive a new attenuation estimation method which uses the analytical backscatter coefficient (BSC) diffraction compensation function for single-element transducers proposed by Chen et al. and compare it to a reference phantom attenuation estimation method. The accuracy of the two methods was evaluated. The results showed that an accurate attenuation coefficient mean value can be estimated by the two methods presenting a low mean percentile error (MPE<6%). However, the coefficient of variation of the estimates remains higher than the desired values (CV>62%). Moreover, to remove the inherent size of the ROI’s limitation due to the high variability of the estimator, the use of full angular spatial compounding was extended to the estimation of attenuation coefficients and its performance was experimentally evaluated using two physical phantoms. The results suggest that the variance and field of view of attenuation imaging can be significantly improved without sacrificing estimation accuracy. Based on these observations, the analytic diffraction compensation method was applied in an animal model to estimate the mean attenuation value of thyroids lobes. To reduce variability on the estimates, a three neighboring layer spatial compounding approach was applied. The results suggest the mean attenuation value can potentially discriminate a particular pathology on thyroid from malignant and normal tissues. The final conclusions lead to remark the potential of parametric imaging of tissue attenuation by the analytic diffraction compensation method in conjunction with spatial compounding as a useful tool for medical detection and diagnostic.
Keywords: Ultrasonido; Ingeniería biomédica; https://purl.org/pe-repo/ocde/ford#2.02.05